Music in everyday life: an exploration into the various uses of music among restaurant servers in Makhanda - Dlamini, Andile Sakhile (Rhodes University, Faculty of Humanities, Department of Sociology)
Inspired by the theory of practice in everyday life and symbolic interactionist perspectives, this thesis offers an account and analysis of findings from a qualitative study. It aimed to investigate the everyday uses of music among restaurant servers (individuals) in Makhanda, on an intra-level of analysis. It explored music's role in individuals' lives, and how music as an art is influential in constructing their individuality or self in society. Ten in-depth interviews were conducted through face-to-face collaboration and an audio recording device. It was evident that music plays various roles in people's lives. Music, seemingly intertwined with everyday life permits individuals to diversly use music, for instance with tackling their emotions and mood, as an accompaniment to tasks or even a symbol that serves subjective meaning to self, essentially transforming the routinized mundanity of every day.
Keywords: Symbolic interactionism; Everyday life; Music -- Social aspects; Music and youth; Music -- Psychological aspects